2007
DOI: 10.1108/03068290710826396
|View full text |Cite
|
Sign up to set email alerts
|

Economic factors and psychiatric hospital beds – an analysis of historical trends

Abstract: PurposeThe purpose of this paper is to explore the association between economic factors (consumer price index, real gross domestic product per capita, base discount rate, and rate of unemployment) and numbers of hospital psychiatric beds.Design/methodology/approachTime series analytical techniques (unit root and cointegration tests) were applied to two regional data sets from the nineteenth century (North Carolina, USA; Berkshire, UK) and three national data sets in the twentieth century (US; UK; Italy) to tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Notably, the results of the random-effects model show a significant variation in the magnitude and direction of the association between countries. This variation cannot sufficiently be explained by socioeconomic indicators such as the GINI coefficient, GDP, or unemployment rates alone [ 18 ]. These results corroborate previous observations that the consequences of deinstitutionalization of the mental health system vary across countries likely due to specific features of their social welfare and health care system, national traditions, socio-cultural context, and the level of available resources [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the results of the random-effects model show a significant variation in the magnitude and direction of the association between countries. This variation cannot sufficiently be explained by socioeconomic indicators such as the GINI coefficient, GDP, or unemployment rates alone [ 18 ]. These results corroborate previous observations that the consequences of deinstitutionalization of the mental health system vary across countries likely due to specific features of their social welfare and health care system, national traditions, socio-cultural context, and the level of available resources [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to the number of psychiatric hospital beds, a recent analysis of time series from the 19th and 20th centuries in Italy, England, and the United States has suggested macroeconomic factors as a main driver for more investments in hospital beds or reductions in their numbers (10). Similar analyses would be welcome for new forms of institutionalized care, but they require series of reliable data, which cannot be obtained for most countries, especially for the crucial categories of residential care and supervised and supported housing.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 Further research pointed toward a potential role of the economy and suggested that both the numbers of psychiatric beds and the sizes of prison populations might be driven by macroeconomic factors. 9,10 Since the 1960s, the numbers of psychiatric beds decreased substantially in most Western countries. It has been suggested that, with regard to deinstitutionalization, the United States failed to reinvest the funding that would have been spent on mental hospitals in new services in the community.…”
mentioning
confidence: 99%